Exploring How Personality Affects Privacy Control Behavior on Social Networking Sites - Li, Yuhui; Huang, Zhaoxing; Wu, Yenchun Jim; Wang, Zhiqiang (Frontiers in Psychology, 2019)
Few studies have examined the relationship between personality traits and social networking sites (SNSs) with a dominant concentration on the personality alterations under SNSs influence. The relationship between personality and privacy control was less focused and discussed. In order to figure out the internal mechanism of such link among youth SNSs users, the Theory of Planned Behavior (TPB) was extended by including Five-Factor Model of Personality to explore how personality traits interact with privacy control behavior on SNSs. The investigation using the theoretical method mentioned led to several hypotheses which were later assessed by an online study conducted within randomly chosen college students (N = 201) from two randomly chosen universities in China. This sampling strategy was designed to mimic the situation of targeted research population in the most reasonable way. The results suggested neuroticism and openness predicted SNSs privacy. Neuroticism and openness predicted “networked privacy” was also found. Theoretical implications of these findings were addressed.